Effectiveness of Family-Centered Oral Health Promotion on Toddler Oral Health in Hong Kong. (March 2022) - Yu, K.F.; Wen, W.; Liu, P.; Gao, X.; Lo, E.C.M.; Wong, M.C.M.
Early childhood caries is common in Hong Kong, and parental practices on maintaining good oral health of their young children are far from satisfactory. This article reports on the effectiveness of a randomized controlled trial on family-centered oral health promotion to new parents in establishing proper feeding habits and oral hygiene practices and in reducing caries risk among 3-y-old toddlers. At baseline, pregnant mothers and their husbands were recruited and randomly allocated into 2 groups. The test group received individualized oral health education (OHE) via a behavioral and educational counseling approach while the control group received the OHE pamphlets only. Information related to the feeding habits, oral hygiene practices, and oral health of the toddlers was collected by parent-completed questionnaires and oral examination annually via home visits. A total of 580 families were recruited at baseline, and 436 toddlers were followed up when they reached 3 y old (test, n = 228; control, n = 208; follow-up rate, 75.2%). The proportions of toddlers who held food in the mouth, fell asleep when milk feeding, had prolonged use of the nursing bottle, ate before bed, and consumed a sweet snack daily were significantly lower in the test group than in the control group (all P  < 0.05). Significantly higher proportions of toddlers brushed their own teeth twice daily, were brushed by their parents twice daily, and used fluoride toothpaste than in the control group (all P  < 0.001). Toddlers in the test group had better oral health status with a lower level of visible plaque, Streptococcus mutans, white spot lesion, and cavitated lesion (all P  < 0.05). Family-centered oral health promotion and individualized OHE for parents via a behavioral and educational counseling approach are more effective in establishing good feeding habits and parental toothbrushing practices and in decreasing the caries risk of their toddlers than the distribution of OHE pamphlets alone (ClinicalTrials.gov NCT02937194).